(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2018)
Jongo Mamulengowas created in 2016. It is a partnership between Bonobando Collective, Jongo da Serrinha and Cordão do Boitatá. On stage are jongo, samba and mamulengo, assets of Brazilian cultural. The narrative traverses several stories of jongoin the Serrinha favela and its relation with the foundation of Império Serrano in 1947. To understand the creative processes in Jongo Mamulengoit is necessary to observe the interplay between the ritual and cosmological dimensions of the actions and representations of mamulengoas a whole. It chose to emphasize the forms, devices, strategies and techniques present in mamulengo. One of the keys to this conception is the notion of brincadeira(game).